Art, creativity, living - Caldwell, Lesley; Milner, Marion, 1900-1998 (Winnicott studies monograph series., 2000)
This volume in the Winnicott Studies series is dedicated to the life and work of Marion Milner and reflects, in varying ways, her unique use of Winnicott's work to shape her own thinking about art and creativity. The collection of papers contained within include contemporary reviews of Milner's books by both Winnicott himself and the poet W.H. Auden, as well as contemporary papers by Adam Phillips, Ken Wright and Lesley Caldwell, amongst others, that testify to the continued work of the Squiggle Foundation in London.